Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1152/ajpheart.01105.2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and sex on the pressor response following a spontaneous burst of muscle sympathetic nerve activity

Abstract: The sympathetic nervous system is critical for the beat-to-beat regulation of arterial blood pressure (BP). Although studies have examined age- and sex-related effects on BP control, findings are inconsistent and limited data are available in postmenopausal women. In addition, the majority of studies have focused on time-averaged responses without consideration for potential beat-to-beat alterations. Thus we examined whether the ability of muscle sympathetic nerve activity (MSNA) to modulate BP on a beat-to-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 49 publications
8
81
2
Order By: Relevance
“…In this regard, Wallin and Nerhed (33) identified clear pressor responses following spontaneous MSNA bursts using a spike-triggered averaging approach to assess beat-by-beat changes in diastolic BP following individual MSNA bursts. We recently extended these findings to describe TVC decreases associated with the BP rise following MSNA bursts as well as clear blunting of these responses with advancing age (31). In the present study, we adapted the spike-triggered averaging method to include simultaneously acquired beat-by-beat femoral vascular conductance measures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, Wallin and Nerhed (33) identified clear pressor responses following spontaneous MSNA bursts using a spike-triggered averaging approach to assess beat-by-beat changes in diastolic BP following individual MSNA bursts. We recently extended these findings to describe TVC decreases associated with the BP rise following MSNA bursts as well as clear blunting of these responses with advancing age (31). In the present study, we adapted the spike-triggered averaging method to include simultaneously acquired beat-by-beat femoral vascular conductance measures.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, we used a spike-triggered averaging approach similar to that used by Wallin and Nerhed when they demonstrated for the first time that arterial blood pressure (BP) transiently increased following MSNA bursts (33). Our laboratory recently extended this work by showing that the BP responses following MSNA bursts are primarily mediated by decreases in total vascular conductance (TVC) and that the magnitude of the pressor response is positively related to the size of MSNA bursts (31). In the present study, we determined to what degree the skeletal muscle vasculature contributes to TVC decreases and arterial BP rises following spontaneous MSNA bursts.…”
mentioning
confidence: 78%
“…The effects of aging on exercise-induced increases in blood pressure remain equivocal, with some studies revealing an exaggerated response in the elderly (17,18), whereas others have found no difference across age groups (24,30,32,56). Since the MAP response to both absolute and relative exercise intensities was similar in both groups (Fig.…”
Section: Aging and The Exercise Pressor Reflexmentioning
confidence: 97%
“…The changes in BP measured using the Finometer have been shown to provide an accurate estimate of directly measured intra-arterial BP (18,46). Also, an automated sphygmomanometer (Welch Allyn, Skaneateles Falls, NY) recorded resting BP by the auscultation of the brachial artery of the right arm for absolute values of BP and to validate BP measurements from the Finometer (7,54). Respiratory movements were monitored using a strain-gauge pneumograph placed around the abdomen (Pneumotrace, UFI, Morro Bay, CA) to avoid potential confound of large respiratory excursions on cardiovascular measurements during handgrip and PEI.…”
Section: Subjectsmentioning
confidence: 99%
“…Multiunit postganglionic MSNA was recorded using standard microneurographic techniques, as previously described (13,36,53,54). Briefly, a tungsten microelectrode was placed into the peroneal nerve near the left fibular head, and a reference microelectrode was inserted 2-3 cm away.…”
Section: Subjectsmentioning
confidence: 99%